35 Student aspih (saspih): the saspih eportfolio system for developing undergraduate simulation and technology-enhanced learning educators. (17th November 2016) - Hine, T; Gopal, A
Abstract : Background: The Association for Simulated Practice in Healthcare's (ASPiH) 1 student branch, Student ASPiH (sASPiH) 2 is devoted to recruiting, retaining and developing undergraduate healthcare professionals within ASPiH. Currently there is no formalised system for developing undergraduate educators within ASPiH. Portfolio systems are extensively employed by other medical organisations to help members record evidence of experience and competence. 3 Due to the diversity of undergraduate healthcare education throughout the UK, a portfolio system for gathering a plethora of different forms of evidence to demonstrate experience and competence would be most suitable. We aim to produce an electronic portfolio (ePortfolio) system to address this need. Methodology: Based on focused group feedback, we have produced a novel ePortfolio system, with a focus on accessibility and ease-of-use for undergraduates. This system will be piloted with sASPiH to those who wish to take part during Summer 2016 with a fast feedback loop, with an aim to ensure it will be ready for the annual ASPiH conference in November 2016; where it will be presented in full and made available for all members. Anticipated outcomes: The ePortfolio will provide a free and convenient means for undergraduate educators using simulation and TEL to record their experience and provide evidence of training and competency. With regards to the latter we intend to link it to the upcoming ASPiH standards for Simulation-based Education in the near-future to expose and develop undergraduates in evidence-based simulation practice, preparing them for postgraduate practice and capturing their experiences. Potential impact: We hope that undergraduates within ASPiH will find the introduction of the ePortfolio beneficial to both their career development as an educator, both enabling them to maximise their own potential and also providing evidence for use in the future. References: ASPiH. Background [Internet]. ASPiH 2016. [Cited May 2016]. Available: http://www.aspih.org.uk/Background/ Gopal AA, Pendleton M, Cox DR. Creating Student ASPiH (sASPiH): Proposed business platform model – establishing a viable, resilient and accountable student branch of ASPiH. BMJ STEL 2014;1 (Suppl1):A82–A83. Tartwijk J, Driessen EW. Portfolios for assessment and learning: AMEE Guide no, 45. Med Teach 2009;31 (9):709–801.